Constraints from high-precision measurements of the cosmic microwave background: the case of disintegrating dark matter with Λ or dynamical dark energy. Issue 2 (8th February 2022) - Liu, Wenzhong; Anchordoqui, Luis A.; Valentino, Eleonora Di; Pan, Supriya; Wu, Yabo; Yang, Weiqiang
Abstract: In recent years discrepancies have emerged in measurements of the present-day rate of expansion of the universe H 0 and in estimates of the clustering of matter S 8 . Using the most recent cosmological observations we reexamine a novel model proposed to address these tensions, in which cold dark matter disintegrates into dark radiation. The disintegration process is controlled by its rate Q  = αℋρddm, where α is a (constant) dimensionless parameter quantifying the strength of the disintegration mechanism and ℋ is the conformal Hubble rate in the spatially flat Friedmann-Lemaître-Robertson-Walker universe and ρddm is the energy density of the disintegrating cold dark matter. We constrain this model with the latest 2018 Planck temperature and polarization data, showing that there is no evidence for α≠ 0 and that it cannot solve the H 0 tension below 3σ, clashing with the result obtained by analyzing the Planck 2015 temperature data. We also investigate two possible extensions of the model in which the dark energy equation-of-state parameter w ≠ -1. In this case it is possible to combine Planck data with the SH0ES measurement, and we demonstrate that in both these models the H 0 tension is resolved at the 1σ level, but the condition w ≠ -1 exacerbates the S 8 tension. We also demonstrate that the addition of intermediate-redshift data (from the Pantheon supernova type Ia dataset and baryon acoustic oscillations) weakens the effectiveness of all these models to address the H 0 and S 8 tensions.